Aquatic Macroinvertebrate Based Preliminary Biomonitoring of the Karo and Koina Rivers of Saranda Region in West Singhbhum District, Jharkhand, India - Pachu, Anish V.; Kumar, Sudhir; Mohan, V.; Kunhikannan, C. (Indian Forester, 2017)
The objective of the study was to assess biological water quality using Macroinvertebrate Water Quality Index (MWQI) of the two rivers- the Karo and Koina originating from Saranda forest region which are crippled by numerous open cast iron ore mining in watersheds of their catchments. The sampling for the analysis was done in three prevailing seasons for a period of one year. A total of 2321 individuals of macro fauna belonging to 65 taxa of 55 families and 14 orders were recorded. Trichoptera was the highest numerically abundant taxa followed by Ephemeroptera and Mesogastropoda. Highest richness of families was recorded in Hemiptera followed by Odonata. The abundance and richness of total macroinvertebrate taxa showed increasing trend from summer to late winter sampling in both the rivers. While significant variance was observed in macro faunal abundance between seasons, their spatial abundance did not vary significantly. The Shannon, Simpson and Margalef indices of their diversity were observed to behigh in late winter sampling compared to that of the other two seasons. Based on MWQI, the water quality characteristics of the rivers varied between ’fair’ with significant organic pollution and ’poor’ with very significant organic pollution. The results of the study indicated seasonal water quality changes in the rivers that mainly attributed to factors resulting from mining and allied activities in the catchments.